EFFECTIVENESS AND COMPETITIVENESS OF FAMILY FARMS IN THE SUBREGIONOF BYDGOSZCZ - Roman Sass (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2018)
The paper aims to determining the farms’ capabilities to develop measured with their technical andfinancial effectiveness as well as the investments’ net volume. The research covers the farms from theBydgoszcz’s sub-region (former province of Bydgoszcz) which prior to accession to the European Union tookadvantage of preferential loans. At the same time in the years 2004-2015 they uninterruptedly conductedaccountancy in the Polish FADN system. The technical effectiveness of the farms has been determined withthe use of the non-parametric DEA method – Data Envelopment Analysis, while for the purposes of thefinancial standing of farms’ analysts, there has been used the value creation index. In order to determinefarms’ development capacity (competitive farms) the Boston Consulting Group (BCG) modified matrix hasbeen applied. It results from the conducted studies, that in the best situation are the farms which have beenrated among the group of leaders, as were characterised by the highest technical and financial effectivenessand also the highest level of net investments. The endangered farms are in the worst situation. In spite ofthe fact that these farms’ technical effectiveness was high, the developmental restrictions result from lowscale of production. Competitiveness of farms is closely connected with their area.